2019
DOI: 10.1016/j.amepre.2019.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Periods for the Association Between Childhood Maltreatment and BMI

Abstract: Introduction: Although previous research has suggested a positive association between child maltreatment and body mass index (BMI) over the life course, it is unclear when the relationship develops. Methods: The authors used time-varying effect models and data from a nationally representative, longitudinal, cohort study (Add Health), to test how childhood physical, sexual, and emotional abuse uniquely varied in associations with BMI from age 13-28, and whether different patterns existed for males and females. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
2
4
1
Order By: Relevance
“…Positive associations between childhood maltreatment and CVD subtypes and BMI have been reported extensively 5,36 but associations with other CVD risk factors such as blood pressure and lipids are less established. 36 We replicated previously observed associations between maltreatment increasing BMI [32][33][34] , smoking behaviour 6,37 , and decreasing SBP. 38,39 Interpretability of interactions and effect modifications Interaction and effect modification are terms commonly used interchangeably despite representing subtly different concepts.…”
Section: Results In Contextsupporting
confidence: 85%
See 2 more Smart Citations
“…Positive associations between childhood maltreatment and CVD subtypes and BMI have been reported extensively 5,36 but associations with other CVD risk factors such as blood pressure and lipids are less established. 36 We replicated previously observed associations between maltreatment increasing BMI [32][33][34] , smoking behaviour 6,37 , and decreasing SBP. 38,39 Interpretability of interactions and effect modifications Interaction and effect modification are terms commonly used interchangeably despite representing subtly different concepts.…”
Section: Results In Contextsupporting
confidence: 85%
“…Reports of sex differences in the association between childhood maltreatment subtypes and CVD have been mixed, 6,13,[32][33][34][35] however we did not identify any sex-specific differences. Replication and validation using other cohorts may elucidate whether we missed modification and sex-specific effects due to lack of statistical power.…”
Section: Results In Contextcontrasting
confidence: 83%
See 1 more Smart Citation
“…We also noted that the effect of childhood exposures to sexual violence on elevated BMI, overweight/obesity/adiposity manifests during sensitive periods of adolescent development into early adulthood. Scholarship has focused mainly on elucidating at what developmental periods childhood maltreatment generally impacts elevated BMI and obesity, with late adolescence/early adulthood emerging as a sensitive period [ 9 , 96 ]. For example, Sokol et al, (2018) [ 97 ] tested childhood exposures to physical, sexual, and emotional abuse and found that these yielded different BMI growth trajectories between the ages of 13 to 28 years for males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly neither of these studies included examination of pre-pubertal growth trajectories, thus potential earlier impacts are unknown. In particular, girls’ exposure to sexual abuse between 13 and 17 years was positively associated with BMI in late adolescence to early adulthood, from 19 to 24.5 years of age [ 96 ]. A meta-analysis of over 40 studies reported a higher risk of obesity in adulthood, following exposure to child maltreatment, not childhood/adolescence [ 9 ].…”
Section: Discussionmentioning
confidence: 99%